2017
DOI: 10.1136/bmjopen-2016-013248
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of testing for anti-Helicobacter pyloriIgG in urine forH. pyloriinfection diagnosis: a systematic review and meta-analysis

Abstract: ObjectivesThis meta-analysis aims to systematically measure the potential diagnostic value of anti-Helicobacter pylori IgG in urine for infection diagnosis, using all eligible studies published in English and Chinese languages.DesignThe random effect model was used to analyse the pooled sensitivity, specificity, positive likelihood ratio (PLR), negative LR (NLR), diagnostic OR (DOR), together with the summary receiver operator characteristic curve.SettingLiterature searches of databases including PubMed, EMBAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 43 publications
0
11
0
2
Order By: Relevance
“…Specifically, SIBO can be detected using a lactulose and glucose H2/CH4 breath test [ 27 , 35 , 36 ], although reports indicate a wide range of sensitivity and specificity [ 37 ]. Similarly, H. pylori can be diagnosed with noninvasive urea breath tests, stool antigen test, and serum/urine antibody tests [ 38 ]. The urea breath test, in particular, has a high reported sensitivity and specificity [ 39 ].…”
Section: The Gut-skin Connectionmentioning
confidence: 99%
“…Specifically, SIBO can be detected using a lactulose and glucose H2/CH4 breath test [ 27 , 35 , 36 ], although reports indicate a wide range of sensitivity and specificity [ 37 ]. Similarly, H. pylori can be diagnosed with noninvasive urea breath tests, stool antigen test, and serum/urine antibody tests [ 38 ]. The urea breath test, in particular, has a high reported sensitivity and specificity [ 39 ].…”
Section: The Gut-skin Connectionmentioning
confidence: 99%
“…It has been known since the mid-1950s that -globulins can be detected in urine (10,13). Although not widely studied or reported, urinebased diagnostic tests that detect antibodies have been suggested as a possible noninvasive alternative to diagnose several conditions, such as dengue, Helicobacter pylori infection, hepatitis A and C, human immunodeficiency virus, strongyloidiasis, schistosomiasis, paragonimiasis, and leishmaniasis (11)(12)(13)(14)(15)(16)(17)(18)(19)(20). To the best of our knowledge, there is no published study on detecting anti-SARS-CoV-2 antibodies in urine.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of methods have also been developed for the noninvasive detection of H. pylori infection through spotting of anti- H. pylori IgG or IgA antibodies in blood, serum, saliva and urine [ 128 ]. Regarding the detection of H. pylori infection in urine, a large meta-analysis, including 23 studies and 4963 patients, reported that testing for anti- H. pylori antibodies in urine could be a valuable marker in the diagnosis of H. pylori infection [ 129 ]. However, tests for IgG in urine may remain positive over a long period of time after the therapy of the H. pylori infection, an acknowledged drawback of the method [ 128 ].…”
Section: Noninvasive Methodsmentioning
confidence: 99%